A controlled study of personality traits in female adolescents with eating disorders - Liley, L.; Watson, Hunna; Seah, E.; Priddis, Lynn; Kane, Robert (Wiley-Blackwell Publishing Ltd., 2013)
Background: Among adults, personality traits have been implicated in the development and maintenance of eating disorders (EDs); whether these findings extend to youth is unknown. The aim of this study was to investigate personality traits of adolescents with EDs.Methods: A case-control approach was performed by comparing a clinical group of female adolescents with EDs (n = 23) to a control group of adolescents in the general community (n = 26) on personality traits of inhibited, self-demeaning, and borderline tendency. Controls were frequency-matched to cases on age and sex, were drawn from a similar geographic catchment area, and observed in the same year as clinical cases. Results: The clinical group demonstrated significantly higher scores on self-demeaning (F(1,47) = 41.39, p < .001, η2 = .075), borderline (F(1,47) = 24.50, p < .001, η2 = .093), and inhibited (F(1,47) = 13.33, p = .001, η2 = .014) personality styles. Adjustment for affective symptomatology diminished the strength of these relationships, but personality pathology still demarcated the group with clinical EDs. Conclusions: The well-established link between personality pathology and EDs in adults generalised to adolescents.